COVID-19-free Pathway Provides Safety for Elective Surgery Patients from Hospital-acquired SARS-CoV-2 Infection - Susianto, Oky; Adhi, Mahendratama; Fajar Rochman, Bagus; Hardian, Rapto; Meliandi, Yopi (Majalah Anestesia & Critical Care, 2022)
Background. Elective surgery during the COVID-19 pandemic must continue to prevent a backlog of surgical cases. Several institutions are implementing a COVID-19-free surgical pathway to minimize the risk of SARS-CoV-2 transmission. This study aimed to assess the safety of patients undergoing surgery against hospital-acquired SARS-CoV-2 infections by implementing a COVID-19-free pathway. Methods. This study is cross-sectional of 572 patients who underwent elective surgery with a COVID-19-free pathway. All patients underwent two days of quarantine in the hospital for RT-PCR testing. A negative COVID-19 test result is valid within 48 hours before surgery, and all surgeries were performed in a non-COVID-19 operating room. Age, gender, ASA classification, type of anesthesia, surgery criteria, length of stay, and ICU admission were the baseline characteristics of the patients in this study. The outcome in this study was hospital-acquired SARS-CoV-2 infections after the patient underwent surgery based on COVID-19 symptoms during hospitalization and 14 days after discharge. Results. This study involved 303 males (53%) and 269 females (47%) with a mean age of 40.16 years ± 11.35 years (12 days–84 years). According to the ASA classification, 44 patients (7.7%) ASA I, 450 (78.7%) ASA II, 77 (13.4%) ASA III and 1 (0.2%) ASA 4. Major or complex surgery criteria accounted for 48% (277) of all surgeries. One hundred and fifty-seven patients (27,4%) underwent postoperative hospitalization for 0-3 days, 190 (33.3%) 4-7 days, and 225 (39.3%) had a length of stay ≥ 8 days. None of the patients showed postoperative COVID-19 symptoms. Three patients died postoperatively, but their deaths were not COVID-19 related. Fourteen days after discharge, eight patients (3%) had fever and cough but did not perform the RT-PCR test. These eight patients experienced clinical improvement and recovery. Conclusion. Implementing a COVID-19-free pathway provides safety for patients from hospital-acquired SARS-CoV-2 infections.